STUDI KASUS SUMBER PERMODALAN DAN SISTEM PENGELOLAAN KEUANGANPADA UD. USAHA JAYA DIKOTA TELUKDALAM - Intan Damai Sejahtera Maduwu; Walsyukurniat Zendrato; Hendrik Kuasa Sihura; Arwan Karier Harefa (Jurnal Education and Development, 2022)
Trade business is one of the types of businesses most are in the community and has an important function as well as a very strategic role as a major contributor to the economic strength of the country. This study aims to determine where the source of capital comes from, how the system of financial management that are applied by UD. Usaha Jaya and how financial management system based on the creation of financial reports on UD. Usaha Jaya. The research method used is qualitative research method with case study approach. Data collection techniques using observation, interview and documentation. Data analysis techniques using the stages of data reduction, data presentation, conclusion and verification, the final conclusions. The validity of data using triangulation, reference materials and checking the peer. The object of this research is a trading company UD. Usaha Jaya. The results of this study show that the UD. Usaha Jaya using two sources of capital that is the source of its own capital and sources of capital a bank loan. Financial management system that is applied there are several stages, namely the planning stage, the stage of budgeting, stage asset allocation, stage the most important priority, phase control, and the savings or cash. Financial management system based on the creation of financial reports UD. Usaha Jaya in the year 2019, it is known that the UD. Usaha Jaya manage the finances at their disposal by way of purchase of goods intensively from the sale of every day or with other understanding any proceeds of sale obtained directly used to buy goods trade, especially trade goods is a priority of effort so that profits can be obtained a maximum at the end of the year.